2016
DOI: 10.1097/j.pain.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

iPeer2Peer program

Abstract: Adolescents with chronic pain are often socially isolated, having never met others with chronic pain, and often feel misunderstood by healthy peers. Adolescence is a sensitive period for developing one's sense of self and autonomy, which often occurs in the context of peer relationships. This developmental process is disrupted in adolescents when their chronic pain interferes with their social interactions. Peer mentoring is proposed as a developmentally timely intervention. The aim of this study is to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…Peer mentoring has been associated with improved diverse health outcomes [1315]. However a systematic review on interventions to improve psychological adaptation to chronic disease by adolescents concluded that the efficiency of peer support groups requires more research; in particular how to achieve greater reach and adoption using novel information and communication technologies [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peer mentoring has been associated with improved diverse health outcomes [1315]. However a systematic review on interventions to improve psychological adaptation to chronic disease by adolescents concluded that the efficiency of peer support groups requires more research; in particular how to achieve greater reach and adoption using novel information and communication technologies [16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the informational, physical, emotional and social needs of adolescents with JIA, an online peer mentoring intervention, the iPeer2Peer Program, was developed [13, 18]. The iPeer2Peer Program focuses on pairing an adolescent living with JIA with a trained young person successfully managing JIA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exploring issues of usability and acceptability). 45,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Many focus specifically on the clinical use of Skype, 91,[114][115][116][117][118][119][120][121][122][123] either on its own or in combination with other technologies [e.g. WhatsApp (WhatsApp Inc., Mountain View, CA, USA) messaging 124 or FaceTime 125,126 ].…”
Section: Evidence Relating To the Use Of Virtual Consultationsmentioning
confidence: 99%
“…Other suggestions from families require further consideration, such as social support interventions. For example, there is some early research supporting the feasibility and acceptability of online peer mentoring among youth with mixed chronic pain conditions (Ahola Kohut et al, 2016) However, limited efficacy data are available and this approach has not been examined among youth with headache. Research is needed to determine whether social support interventions are feasible, acceptable, and effective for youth with headache.…”
Section: Discussionmentioning
confidence: 99%